Socio-technological proposal for development of open access repositories adapted to Argentine´s universities context - San Martín, Patricia (2014)
The paper shows the main result of the scientific-technological investigation project “Towards the development and the use of Institutional Repositories of Open Access for Educational Digital Objects in the context of public universities belonging to the mid-east area of Argentina”. Its objective is to design and propose a prior theoretical, methodological and technological model, which is experimental, of Open Access Institutional Repositories for Educational Digital Objects. In view of the theoretical and methodological framework of Dynamic Hypermedial Device, a socio-technological approach was adopted. Therefore, qualitative and software engineering instruments and methodological techniques were implemented. Based on DSpace diagnostics data usability problems and viewing needs and publications practices in open access of the regional academic community, we develop a First Experimental Prototype for Educational Digital Objects with DSpace technology. Design options in terms of internal organization, visibility and usability of the prototype are explained. About the internal organization, 12 collections of various types of Educational Digital Objects were predetermined. Observing the definition of required and optional fields of metadata for each collection combining Dublin Core and Learning Object Metadata metadata standards. About usability, First Experimental Prototype improvement and assessments conducted by academics from the participating universities are presented. These evaluations show an improvement in self-archiving conditions and the possibility to create publication models more efficient, inclusive and open.